Comparison of methodologies based on polarization curves and potentiostatic anodization in the production of TiO2 nanostructures at low potential (Superficies y Vacío, 2012)
In this work we compare the morphology obtained in the synthesis of TiO2 nanostructures at low potential using two electrochemical techniques: polarization curves (CP) and potentiostatic anodization (CA). Before testing, the titanium foil specimens were pretreated differently to homogenize the effect of mechanical polishing. The nanostructures were formed in aqueous solution of hydrofluoric and sulphuric acids at various concentrations. Scanning electron microscopy images showed porous structures with pore diameter of 400 – 700 nm in the CA technique and 200 - 400 nm in the CP technique. In contrast, the thickness of the films was similar and around 1 µm in both techniques. The results indicated that it is possible to form porous arrays of TiO2 with electrochemical and pretreatment methods simpler than those required by potentiostatic anodization.